PERAN STRATEGIS FUNGSI MANAJEMEN MUTU DALAM MENINGKATKAN DAYA SAING SEKOLAH PADA SMAN 5 KOTA SERANG - Rizko Argi Budiaji; Syadeli Hanafi; Cucu Atikah (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2024)
This research aimed to explore the role of quality management in enhancing school competitiveness at SMAN 5 Serang City. The study focused on four key questions: (1) how does educational quality planning improve school competitiveness? (2) How does the implementation of educational quality enhance competitiveness? (3) How does the evaluation process of educational quality contribute to school competitiveness? And (4) what actions are taken during the evaluation process to improve competitiveness? This study used a descriptive qualitative research method with a case study design. Data were collected through in-depth interviews, observations and field notes. Data analysis used narrative analysis from existing data sources. The findings revealed that (1) the planning process for improving educational quality included several strategic steps. (2) Implementation involved meeting targets set in the planning stage, though the school still needed to work on optimizing competitiveness and managing facilities effectively. (3) Educational quality evaluations were conducted through regular monitoring, focusing on the curriculum and human resource development. However, competitiveness and facilities management still need to be improved. (4) The school implemented in-house training and improved school information systems to address these challenges. The researcher recommends further studies on the role of quality management in school competitiveness, either in this location or in different settings. Future research could also focus on other topics in the exact location, such as at SMAN 5 Serang City.